A homozygous ROR2 variant in a family with atypical Robinow syndrome and tetramelic transverse deficiency of autopods. Issue 1 (27th September 2021) - Malik, Sajid; Nalbant, Gökhan; Noreen, Moqadsa; Afzal, Muhammad; Tolun, Aslıhan
Abstract: We present five members of a consanguineous Pakistani kinship with the most severe familial tetramelic transverse autopod deficiency reported to date and additionally having some of the common autosomal recessive Robinow syndrome‐1 (RRS1) features including short stature, short neck, severe vertebral anomalies of kyphoscoliosis, hemivertebrae, fusion of thoracic vertebrae, broad forehead, and dental crowding. We mapped the locus of this atypical RRS and detected homozygous 8‐nucleotide deletion c.1353_1360del (p.(Met452Alafs*4)) in ROR2, the gene responsible for RRS1. We did not find any other variant shared by all affected individuals that could possibly act as a modifier of limb defect. Autopods are affected in RRS1, but severe autopod deficiency is not a characteristic feature. Over 30 biallelic variants dispersed throughout the gene are known in ROR2 ‐related RS, with no genotype–phenotype correlation for specific RRS1 features. Considering together with the sporadic case homozygous for variant p.(Arg442*) and the case homozygous for p.(Arg441Thrfs*16) in a family where heterozygous members have brachydactyly type B1, we propose that homozygous truncating variants that originate at residues 441–452 can cause severe autopod reduction anomalies, suggesting some genotype–phenotype correlation for this particular phenotype.